Comparing Usability of Augmented Reality and Virtual Reality for Creating Virtual Bounding Boxes of Real Objects - Nyan Kyaw; Morris Gu; Elizabeth Croft; Akansel Cosgun (Applied Sciences, 2023)
This study conducts a comparative analysis of user experiences of Augmented Reality (AR) and Virtual Reality (VR) headsets during an interactive semantic mapping task. This task entails the placement of virtual objects onto real-world counterparts. Our investigation focuses on discerning the distinctive features of each headset and their respective advantages within a semantic mapping context. The experiment employs a user interface enabling the creation, manipulation, and labeling of virtual 3D holograms. To ensure parity between the headsets, the VR headset mimics AR by relaying its camera feed to the user. A comprehensive user study, encompassing 12 participants tasked with mapping six tabletop objects, compares interface usability and performance between the headsets. The study participants’ evaluations highlight that the VR headset offers enhanced user-friendliness and responsiveness compared to the AR headset. Nonetheless, the AR headset excels in augmenting environmental perception and interpretation, surpassing VR in this aspect. Consequently, the study underscores that current handheld motion controllers for interacting with virtual environments outperform existing hand gesture interfaces. Furthermore, it suggests potential improvements for VR devices, including an upgraded camera feed integration. Significantly, this experiment unveils the feasibility of leveraging VR headsets for AR applications without compromising user experience. However, it also points to the necessity of future research addressing prolonged usage scenarios for both types of headsets in various interactive tasks.